Numerical Analysis of Ridged-Circular Nanoaperture for Near-Field Optical Disk. (29th October 2013) - Kitamura, Toshiaki
Abstract : A ridged-circular nanoaperture is investigated through three-dimensional (finite-difference time-domain) FDTD method. The motion equations of free electrons are inserted to analyze a metallic material. The electromagnetic field distributions of optical near-field around the aperture are investigated. The phase change disk illuminated by a near-field optical light through a ridged-circular nanoaperture is also analyzed. The far-field scattering patterns from the phase change disk and the crosstalk characteristics between plural marks are studied.